NUTRITIONAL INTERVENTION IN STUNTING CHILDREN AGED 1-5 YEARS-OLD USING ORAL NUTRITIONAL SUPPLEMENTS (ONS) IN SURABAYA CITY - Alexander, Yoppi Yeremia; Widjaja, Nur Aisiyah; Irawan, Roedi; Hanindita, Meta Herdiana; Noviyanti, Tausyiah Rohmah; Keya, Rino Tryanto; Hermanto, Edi; Bahmid, Moh.; Iitdrie, Iitdrie (Universitas Airlangga, 2025)
Growth faltering, also known as failure to thrive, in pediatric populations may arise from a combination of insufficient nutritional intake and the presence of chronic infections. When this condition persists over an extended duration, it can culminate in stunting—a form of chronic malnutrition characterized by impaired linear growth—which continues to exhibit a high prevalence rate across various regions of Indonesia. As part of the national effort to mitigate and prevent stunting, oral nutritional supplements (ONS), which are specifically formulated for both therapeutic and dietary management in pediatric patients with specific health conditions, including growth failure, play a critical role. This study aims to examine the impact of ONS intervention, with a caloric density of approximately 1 kilocalorie per milliliter, on stunted children between the ages of one and five years at a private healthcare facility, namely Husada Utama Hospital in Surabaya. This study is an observational analytical study of a quasi- randomized control trial with a pre- and post-test design. The sample of this study was stunting children aged 1-5 years as many as 20 subjects who were willing to follow the ONS intervention research in achieving optimal growth. After being given intervention for 90 days, the number of normal HAZ/LAZ children became 5 (25% increase). There was a decrease from severely stunting by 7 subjects to stunting and a decrease in stunting to normal by 5 subjects